Myocardial performance index in hypertensive disorders of pregnancy: The relationship between blood pressures and angiogenic factors. (3rd April 2017) - Ramadan, Hadi; Rana, Sarosh; Mueller, Ariel; Bajracharya, Surichhya; Zhang, Dongsheng; Salahuddin, Saira; Nasim, Rabab; Perdigao, Joana Lopes; Minhaj, Mohammed; Tung, Avery; Arany, Zolt; Shahul, Sajid
ABSTRACT: Objective: To study the association between cardiac function measured by myocardial performance index (MPI), blood pressures and angiogenic factors measured at the time of echocardiography in patients with and without hypertensive disorders of pregnancy (HDP). Methods : We prospectively studied 189 pregnant women and evaluated whether changes in cardiac function observed on echocardiography were correlated with higher blood pressures and whether higher blood pressures were associated with antiangiogenic proteins (soluble fms-like tyrosine kinase, sFlt1; soluble endoglin, sEng). Comprehensive echocardiograms, including measurement of MPI, were performed on all patients. sFlt1 and sEng levels were measured using enzyme-linked immunosorbent assay. Results : Overall, 189 patients were divided into tertiles based on mean arterial pressure (MAP). The MPI was worst in tertile 3 (0.50 ± 0.15) compared to tertile 1 (0.42 ± 0.10), p = 0.0004. sFlt1 (pg/ml) and sEng (ng/ml) were highest in tertile 3 compared to tertile 1: 15055.37 vs. 1623.01 and 33.06 vs. 8.15, respectively, with p-value <0.001. In crude multivariate regression analysis, MAP was positively correlated with MPI (r = 0.32, p < 0.001), GLS (r = 0.54, p < 0.001), sFlt1 (r = 0.60, p < 0.001) and sEng (r = 0.61, p < 0.001). After adjustment for confounders, these relationships persisted between MAP and MPI (r = 0.31, p = 0.0003), GLS (r = 0.46, p < 0.001), sFlt1 (r = 0.56, p < 0.001) and sEng (r = 0.58, p < 0.001). Conclusion : Mean arterial pressure correlates with worsening cardiac function as measured by MPI and serum levels of angiogenic factors. Further studies are needed to evaluate whether a reduction in blood pressure will reverse changes in MPI or reduce levels of angiogenic proteins seen among women with HDP.